Perencanaan Transportasi Umum Berbasis Kereta Api (Rute Tanjung Karang - Bandara Radin Inten II) - Mutohir, Rindri; Herianto, Dwi; Pratomo, Priyo (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2017)
Planning a mode of transport could be done in order to know the extent of the effectiveness of the movement of people and goods or use the train through the route of Tanjung Karang - Radin Inten II Airport. In addition, the plan is also aims to reduce the obstacles that often complained by users of transport from Tanjung karang - Radin Inten II Airport which using moda transportation right now. In this study the method used is statistics descriptive, to find utility board based on what’s the way of work or business, a social visit, school, and leisure. Of all respondents filled out the questionnaire, there are 258 (71,67%) of respondents from Bandar Lampung and 102 (28,33%) of respondents came from out Bandar Lampung. It showed that the demand of transport air that comes from Bandar Lampung is higher compared to the number of out Bandar Lampung. The survey also said as many as 86,12% of respondents from Bandar Lampung interest to switch to moda transportation. Keyword: Train, airport train, train schedule, gapeka.